Antibacterial Properties of Lemon Juice–Mediated Zinc Oxide Nanoparticle and Titanium Dioxide Nanoparticle - Mary Sheloni Missier; Mahesh Ramakrishnan; S Veerasankar; C Dhanalakshmi; Harish Ponniah; Shanmugam Rajeshkumar (Journal of Pharmacy and Bioallied Sciences)
Introduction: The emergence of antibiotic-resistant pathogenic bacteria has become a major global health concern, with the increasing prevalence of infections that are difficult to treat with conventional antibiotics. As a result, there is a critical need for alternative antimicrobial agents that can effectively control bacterial infections and combat the growing problem of antibiotic resistance. Materials and Methods: In this study, the antibacterial properties of lemon juice mediated zinc oxide nanoparticles (ZnO NPs) and titanium dioxide nanoparticles (TiO2 NPs) was evaluated against oral pathogens. The synthesized nanoparticles were characterized using UV-Vis spectroscopy. The antimicrobial activity of the nanoparticles was determined by the agar well diffusion assay. Results: Our results showed that both ZnO NPs and TiO2 NPs exhibited potent antimicrobial activity against both Streptococcus mutans and Streptococcus mitis. Our findings suggest that the antimicrobial activity of ZnO NPs and TiO2 NPs is attributed to the disruption of bacterial cell membrane integrity and inhibition of bacterial growth. Conclusion: Therefore, lemon juice mediated ZnO NPs and TiO2 NPs can be considered as promising antimicrobial agents for controlling bacterial infections.